Bioinspired Silk Fibroin Mineralization for Advanced In Vitro Bone Remodeling Models. (7th August 2022) - de Wildt, Bregje W. M.; van der Meijden, Robin; Bartels, Paul A. A.; Sommerdijk, Nico A. J. M.; Akiva, Anat; Ito, Keita; Hofmann, Sandra
Abstract: Human in vitro bone models can create the possibility for investigation of physiological bone remodeling while addressing the principle of replacement, reduction and refinement of animal experiments (3R). Current in vitro models lack cell–matrix interactions and their spatiotemporal complexity. To facilitate these analyses, a bone‐mimetic template is developed in this study, inspired by bone's extracellular matrix composition and organization. Silk fibroin (SF) is used as an organic matrix, poly‐aspartic acid (pAsp) is used to mimic the functionality of noncollagenous proteins, and 10× simulated body fluid serves as mineralization solution. By using pAsp in the mineralization solution, minerals are guided toward the SF material resulting in mineralization inside and as a coating on top of the SF. After cytocompatibility testing, remodeling experiments are performed in which mineralized scaffold remodeling by osteoclasts and osteoblasts is tracked with nondestructive microcomputed tomography and medium analyses over a period of 42 d. The mineralized scaffolds support osteoclastic resorption and osteoblastic mineralization, in the physiological bone remodeling specific sequence. This model could therefore facilitate the investigation of cell–matrix interactions and may thus reduce animal experiments and advance in vitro drug testing for bone remodeling pathologies like osteoporosis, where cell–matrix interactions need to be targeted. Abstract : To develop drugs for bone pathologies like osteoporosis, animal experiments are routinely performed with poor clinical translation. In vitro bone remodeling models could advance preclinical testing, but current models do not include functional outcomes like formation and resorption of bone‐like matrix. Here, a bioinspired remodeling template is developed using biomineralization techniques, which facilitate the investigation of bone remodeling in vitro.